Epidemiology, treatment and outcome after compartment syndrome of the thigh in 69 cases – Experiences from a level I trauma centre. Issue 6 (June 2019) - Rameder, Philipp; Schmidt, Reinhard; Machold, Wolfgang; Tiefenboeck, Thomas M.; Bukaty, Adam; Huf, Wolfgang; Boesmueller, Sandra
Highlights: Compartment syndrome of the thigh a rare condition. Delayed diagnosis and therapy can be associated with severe impairment. High impact trauma leads to highest complication rates. Concomitant femur fractures lead to an increase number of surgical interventions. Abstract: Background: Compartment syndrome of the thigh (CST) is a rare condition, and its delayed diagnosis and therapy may lead to devastating adverse effects. Thus, the aim of this study was to present the amassed clinical experiences, regarding diagnosis and treatment of CST at a level I trauma centre. Materials and methods: The database was reviewed for all patients with a manifest CST treated surgically between 1995 and 2014. Results: 69 patients (61 males and 8 females) met the inclusion criteria, with a mean age of 42.9 years (range: 11–87 years). Forty-four patients (64%) presented with an isolated CST. There was a significant association between complication rates and high impact vs. blunt trauma (12/32, 38% vs. 0/20, 0%; p = 0.0022; Fisher's exact test). The number of surgeries in patients with a concomitant femur fracture was significantly increased (in mean: 2.8 vs. 4.9 surgical interventions; p < 0.001; U test). Conclusion: Patients after high impact trauma showed the highest complication rate. Concomitant femur fractures were associated with an increased number of surgical interventions. The synopsis of trauma mechanism, clinical presentation, age, anticoagulation status and clinical experience of the trauma surgeon seem to be the best tools to correctly diagnose CST.